Effectiveness of an Educational Program on Nurses’ Practices toward Using of Personal Protective Equipment at Kidney Transplant Center in Baghdad City - Anmar Hadi Abbas; Hussein Hadi Atiyah (Institute of Medico-legal Publications Pvt Ltd, 2021)
The study aims to evaluate nurses’ practices toward using personal protective equipment, and to identify therelationships between nurses’ demographics including (age, gender, education level, and years of experiencesin kidney transplantation units) and their practices toward aseptic techniques. A quasi-experimental study,quantitative design (One-group Pretest - Posttest) was conducted on nurse’s practice toward aseptictechniques in kidney transplant units. It was carried out in order to achieve the early stated objectives withthe application of pretest and posttest. A non-probability (purposive) sample of (30) nurses who are workingin kidney transplant unit, that’s selected based on the study criterion, and after obtaining oral consent fromthem, those nurses were distributed in kidney transplant units at Medical City complex. The study Instrumentwas composed of two Parts: The First Part is concerned with the socio-demographic characteristics, and thesecond Part includes Nurses’ Practices. Content validity of the instrument was established through a penalof (12) experts. Reliability of the instrument scales determined the internal consistency by using test-retestapproach through the computation of Pearson correlation coefficient of the scale which was r=0.83 for nurse’practices. Results have been analyzed through the use of SPSS “Statistical Package for Social Sciences”model 24.0 by using descriptive and inferential statistical methods. Findings of the present study revealedthat most of the samples were within the age of (40 - 49) years who were accounted (40%). It has beenpresented that there were significant differences in the mean of the study sample between the pre and post testprocedures, revealing a significant improvement in nurses’ practices regarding using of personal protectiveequipment. Moreover, a high significant difference was also presented among the whole study sample at preand post-test practices, t-test value (8.462) at p value (.000). The study recommended that nurses shouldbe committed to follow and apply standards of using the personal protective equipment, sharing in trainingsessions, improve practices through self-learning and training, and establishing future studies to measurenurses’ practices toward using personal protective equipment at all healthcare settings in Iraq.